The Effect of Loneliness on Narcissistic Tendencies with Self Disclosure As A Moderating Variable among Adult Social Media Users - Suraya, Intan; Imawati, Diana; Umaroh, Siti Khumaidatul (MOTIVA: JURNAL PSIKOLOGI, 2025)
The development of digital technology has increased every year, one of which is the use of social media. Social media creates a new space for self-presentation, which in turn poses psychological challenges such as loneliness and narcissistic tendencies. This study aims to examine the effect of loneliness on narcissistic tendencies with self-disclosure as a moderating variable. A quantitative approach and survey method were employed, using a non-probability sampling technique, specifically quota sampling. The study involved 503 respondents aged 18–40 years who were active users of social media platforms such as Facebook, Instagram, and TikTok. The analysis results indicate that loneliness has a significant influence on narcissistic tendencies, with a significance value of 0.000 and a coefficient of determination (R Square) of 0.187. This suggests that the higher the level of loneliness experienced by an individual, the higher their narcissistic tendencies. Furthermore, the results of the moderation test showed a significance value of 0.000 with a correlation (R Square) of 0.580. This means that individuals who experience loneliness and have a high level of self disclosure tend to exhibit stronger narcissistic behaviors.